2014
DOI: 10.1097/mph.0000000000000260
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Hemangiomas, Vascular Malformations, and Primary Lymphedema

Abstract: With improved genetic testing and genomic sequencing, abnormalities are increasingly being identified in affected or germline tissues in DNA of patients with vascular tumors, vascular malformations, and lymphedema. Recognition of the genetics of vascular anomalies should help clinicians make more specific diagnoses, anticipate diagnosis-specific morbidities, provide better genetic counseling, and have a better understanding of the pathogenesis of these anomalies. Growing pharmacologic options, including therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Also, the wild‐type and mutant forms of TIE2 are known to signal partially through the mitogen‐activated protein kinase (MAPK) signalling pathway in endothelial cells . It is of note that the MAPK signalling pathway has also been found to be overactivated in VAs by genetic mutation of its components or by indirect alterations , but this will not be described further in the present review.…”
Section: Activation Of Pi3k Pathway Components In Vasmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the wild‐type and mutant forms of TIE2 are known to signal partially through the mitogen‐activated protein kinase (MAPK) signalling pathway in endothelial cells . It is of note that the MAPK signalling pathway has also been found to be overactivated in VAs by genetic mutation of its components or by indirect alterations , but this will not be described further in the present review.…”
Section: Activation Of Pi3k Pathway Components In Vasmentioning
confidence: 99%
“…PHACE syndrome: posterior fossa malformations, haemangioma, arterial anomalies, cardiovascular anomalies, and eye anomalies; and LUMBAR syndrome: lower body haemangioma, urogenital anomalies, ulceration, myelopathy, bony deformities, anorectal malformations, arterial anomalies, and renal anomalies) . Although our genetic understanding of VAs is increasing, with additional associations being described , at present the classification system remains based primarily on clinical, radiological and histological features; however, it is likely that further refinement will occur with additional distinction of cases on the basis of underlying genetic mechanisms, as illustrated here.…”
Section: Vascular Anomaly (Va) Classificationmentioning
confidence: 99%
“…12,13 Approximately 30 different genes have been documented in the literature so far in association with vascular anomalies addressing the putative role of allelic, phenotypic, and locus heterogeneity in genesis of vascular lesions. 12 In particular, it has been reported that mutations in GNAQ and GNA11 genes were associated with congenital hemangiomas, 14,15 mutations in BMP9/10 and ALK1 genes were associated to sporadic venous malformations, 16,17 while mutations within the TEM8 and VEGFR2 genes were reported to confer susceptibility to infantile hemangiomas. 18 Tumors often contain genetically diverse, subclonal populations of cells, 19,20 and heterogeneity in tumor evolution is a key factor for neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…The selected genotyping platform covered the entire genome with a CNV detection rate of ∼30 to 50 kb and benefit from the fact that we targeted an enriched region with an additional cut-off detection rate as low as 300 bp of 1989 specific genes, including genes within the vasculogenesis signaling pathway, which have previously reported to be implicated in the pathogenesis of infantile hemangiomas and vascular malformations. 12,13 Approximately 30 different genes have been documented in the literature so far in association with vascular anomalies addressing the putative role of allelic, phenotypic, and locus heterogeneity in genesis of vascular lesions. 12 In particular, it has been reported that mutations in GNAQ and GNA11 genes were associated with congenital hemangiomas, 14,15 mutations in BMP9/10 and ALK1 genes were associated to sporadic venous malformations, 16,17 while mutations within the TEM8 and VEGFR2 genes were reported to confer susceptibility to infantile hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
“…The exact cause remains unknown; however, gravity probably exacerbates the problem and contributes to its progression. 6 7 8 9 Secondary lymphedema refers to lymphedema caused by obstruction or destruction of normally formed and developed lymphatic channels or nodes. This can occur following trauma, radiation, infection, or surgery.…”
Section: Introductionmentioning
confidence: 99%